Geometric Isomers and Cytotoxic Effect On T47D Cells of Curcumin Analogues PGV-0 and PGV-1 - Edy Meiyanto; Muhammad Da'i; Supardjan A. M.; Umar Anggara Jenie (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
Curcumin analogues 2,5-bis-(4’-hidroxy-3’-methoxy)-benzilidinecylopentanone (PGV-0) and 2,5-bis-(4’hidroxy-3’,5’-dimethyl)-benzilidinecylopentanone (PGV-1) have a potency to be developed as cytotoxic agent. The aims of this research are to elucidate the geometric isomer and to study the cytotoxic effect on T47D cells of both compounds. To establish the geometric isomer these compounds, they were elucidated by LC-MS, 1H-NMR, 13C-NMR, HMBC, HMQC, NOESY. Their cytotoxic effect were evaluated by MTT assay method on T47D cells. The results concluded that the geometric isomer of PGV-1 is zusammen-zusammen (Z-Z) and PGV-0 is entgegen-entgegen (EE). The IC50 of both compounds are 1.74 and 9.39 μM respectively.Key words: PGV-0, PGV-1, Cytotoxicity